Discovery of Novel Variants on the CHD7 Gene: A Case Series of CHARGE Syndrome - Wu, Xiangtao; Chen, Liang; Lu, Weihong; He, Shaoru; Li, Xiaowen; Sun, Lingling; Zhang, Longjiang; Wang, Dejuan; Zhang, Ruigui; Liu, Yumei; Sun, Yunxia; Feng, Zhichun; et al. (Frontiers in Genetics, 2022)
Background: CHARGE syndrome (CS) is a single-gene genetic disorder with multiple organ malformations caused by a variant of the Chromodomain helicase DNA-binding protein 7 (CHD7) gene on chromosome 8q12.1. In this study, we aim to investigate new variants that have emerged in these cases compared with typical CS and the relationship between the genes and phenotypes. Methods: Patients with suspected genetic disease were subjected to WES at a genetics laboratory in Guangzhou. The average sequencing coverage depth was > 200 ×, and 96% was > 20 ×. Variant interpretation was manipulated according to the American College of Medical Genetics (ACMG) guidelines.Molecular data on databases for ClinVar and CHD7 were also collected and collated. We reviewed the currently described CHD7 variants and analysed the genetic variation and phenotypic heterogeneity. Results: Data of 12 patients with CS from four hospitals in China were collected. According to gestational age, most of them (8/12) were near-term babies with a lower birth weight than their peers, averaging 2.62 kg. In this study, the most common phenotypes were respiratory tract malformations (11/12), heart malformations (10/12) and central nervous system malformations (9/12).Two foetuses were confirmed to have brain or heart abnormalities during prenatal testing, while 10/12 were found to have abnormalities during prenatal testing. The maximum Acute Physiology and Chronic Health Evaluation (APACHE II) score at admission was 19 and the average was 11.58. Five variants in the CHD7 gene c.7012C>T(p.Q2338*), c.7868delC(p.P2623Rfs*16), c.5405-3C>G, c.6936+2T>C,c.8077-2A>G ) were novel and were located in exons 33, 36and intron 25, 32,37 respectively. There may be a positive correlation between exon location and phenotype. Conclusion: Five novel variants were discovered. These expanded the mutational spectrum of the CHD7 gene and the phenotype of CS. There may be a correlation between the new mutation sites and the phenotype, which has some reference value for evaluation of mutation sites.